Like Father, like Son? - Malika Dekkiche (Medievalista)
Against the assumption that premodern diplomacy was mostly taking place among equals, this article aims to investigate several cases of parallel diplomacy during the 15th century between the Timurids, the Qara Qoyunlu and the Mamluk sultanate in Cairo. While during the previous period official rulers were indeed dominating the diplomatic stage, it seems that in the fifteenth century, members of their family (sons and even grandson) also took part in the game. The paper aims to present those cases and highlight the importance of diplomatic letter collection for the study of intra-Muslim contacts beyond the sultans.